Gut Microbiota-Derived Resveratrol Metabolites, Dihydroresveratrol and Lunularin, Significantly Contribute to the Biological Activities of Resveratrol - Li, Fang; Han, Yanhui; Wu, Xian; Cao, Xiaoqiong; Gao, Zili; Sun, Yue; Wang, Minqi; Xiao, Hang (Frontiers in Nutrition, 2022)
Although resveratrol (RES) is barely detectable in the plasma and tissues upon oral consumption, collective evidence reveals that RES presents various bioactivities in vivo, including anti-inflammation and anti-cancer. This paradox necessitates further research on profiling and characterizing the biotransformation of RES, as its metabolites may contribute profound biological effects. After 4-week oral administration, eleven metabolites of RES were identified and quantified in mice by HPLC-MS/MS, including dihydro-resveratrol (DHR), lunularin (LUN), and conjugates (sulfates and glucuronides) of RES, DHR and LUN. Importantly, DHR, LUN, and their conjugates were much more abundantly distributed in tissues, gastrointestinal tract (GIT), and biological fluids compared to RES and its conjugates. Moreover, we established that DHR and LUN were gut bacteria-derived metabolites of RES, as indicated by their depletion in antibiotic-treated mice. Furthermore, the biological activities of RES, DHR, and LUN were determined at physiologically relevant levels. DHR and LUN exhibited stronger anti-inflammatory and anti-cancer effects than RES at the concentrations found in mouse tissues. In summary, our study profiled the tissue distribution of the metabolites of RES after its oral administration in mice and uncovered the important role of gut microbial metabolites of RES in the biological activities of RES in vivo.